The protein Ocular albinism 1 is the orphan GPCR GPR143 and mediates depressor and bradycardic responses to DOPA in the nucleus tractus solitarii. (January 2014) - Hiroshima, Y; Miyamoto, H; Nakamura, F; Masukawa, D; Yamamoto, T; Muraoka, H; Kamiya, M; Yamashita, N; Suzuki, T; Matsuzaki, S; Endo, I; Goshima, Y
<x xml:space="preserve">Abstract</x> Background and Purpose L‐DOPA is generally considered to alleviate the symptoms of Parkinson's disease by its conversion to dopamine. We have proposed that DOPA is itself a neurotransmitter in the CNS. However, specific receptors for DOPA have not been identified. Recently, the gene product of ocular albinism 1 (OA1) was found to exhibit DOPA‐binding activity. Here, we have investigated whether OA1 is a functional receptor of DOPA in the nucleus tractus solitarii (NTS). Experimental Approach We examined immunohistochemical expression of OA1 in the NTS, and the effects of DOPA microinjected into the depressor sites of NTS on blood pressure and heart rate in anaesthetized rats, with or without prior knock‐down of OA1 in the NTS, using shRNA against OA1. Key Results Using a specific OA1 antibody, OA1‐positive cells and nerve fibres were found in the depressor sites of the NTS. OA1 expression in the NTS was markedly suppressed by microinjection into the NTS of adenovirus vectors carrying the relevant shRNA sequences against OA1. In animals treated with OA1 shRNA, depressor and bradycardic responses to DOPA, but not those to glutamate, microinjected into the NTS were blocked. Bilateral injections into the NTS of DOPA cyclohexyl ester, a competitive antagonist against OA1, suppressed phenylephrine‐induced bradycardic responses without affecting blood pressure responses. Conclusion and Implications OA1 acted as a functional receptor for DOPA in the NTS, mediating depressor and bradycardic responses. Our results add to the evidence for a central neurotransmitter role for DOPA, without conversion to dopamine.